Visual and Narrative Content Variation in Building Consumer Trust: A Case Study of Ecinos' Social Media Strategy - Lovjoyla Lennial; Christian (Universitas Multimedia Nusantara, 2026)
This study examines how visual and narrative content variation contributes to consumer trust and purchase intention in local fashion branding. Focusing on Ecinos as a case study, the research explores how promotional content, informative posts, storytelling, and value-driven campaigns operate as communication strategies on social media. This study employs a qualitative single-case study approach grounded in a qualitative constructivist paradigm and supported by descriptive data triangulation. Data were collected through a preliminary perceptual survey involving 55 Instagram users, in-depth interviews with two digital content practitioners and two fashion content creators, and observational analysis of Ecinos’ social media content. The survey was used only to identify general audience tendencies and was not intended for inferential or causal claims. The findings indicate that varied content supports trust formation when it combines visual consistency, process transparency, relevant information, and humanized storytelling. Behind-the-scenes content helps reduce audience uncertainty by revealing production processes and product value, while inclusive and socially meaningful narratives foster emotional connection and community identification. The study concludes that, in local fashion branding, social media content design functions not only as a promotional tool but also as a trust building communication strategy. The findings contribute to visual communication design studies by showing how content variation can transform product-centered communication into a more authentic and relationship-oriented brand experience.